Entrelaçando histórias de vida e sentimentos de pertencimento: reflexões da formação permanente de uma professora alfabetizadora - Silva, Felipe Costa da (2023)
This work is linked to the Research Line "Teaching, Knowledge and Professional Development" of the Graduate Program in Education at the Federal University of Santa Maria, Master in Education. The main objective of this study is to understand how the life story of a teacher literacy teacher of the Public Education Network influences her pedagogical practice, taking into account her notes from the field of memory. The specific objectives will be: to know the life story and trajectory of a literacy teacher of the Public Education Network; between memories of the formative trajectory influenced the pedagogical practice of this teacher; perceive how her formative trajectory helped in the construction of her identity, committed to citizenship and social transformation. The methodology is based on a research with a qualitative approach, linked to the stories of life and the methodological practices of a teacher from one to literacy teacher in the public school system in the municipality of Santa Maria (RS). It is anchored in the understanding of life stories as a methodological process, presupposing approaches linked to teaching and the threads that lead this knowledge based on narratives, anxieties and considerations that hope is the understanding of a life history moved by teaching. The collaborator of this research is a literacy teacher/early years of the municipal and state network, in the municipality of Santa Maria/RS, with 25 (twenty-five) years of experience in public education.